2015
DOI: 10.1177/0034355215590770
|View full text |Cite
|
Sign up to set email alerts
|

Application of the KVI-R to Assess Current Training Needs of Private Rehabilitation Counselors

Abstract: The primary purpose of this mixed-methods study was to identify the current training needs of rehabilitation counselors in the private sector. Four hundred twenty-six participants completed the Knowledge Validation Inventory–Revised. The self-reported needs for training are reported across the 10 knowledge domains of rehabilitation counseling. The overall training needs (TN) score for the sample was moderate. For the broader knowledge domains, respondents reported the highest mean TN scores for Case Management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The literature indicates rehabilitation counselors both need and want a broader knowledge base and skillset to prepare them to work with a diverse clientele (Beveridge et al, 2016;Zanskas & Leahy, 2007).…”
Section: Diversity and Multiculturalismmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature indicates rehabilitation counselors both need and want a broader knowledge base and skillset to prepare them to work with a diverse clientele (Beveridge et al, 2016;Zanskas & Leahy, 2007).…”
Section: Diversity and Multiculturalismmentioning
confidence: 99%
“…A study by Beveridge et al (2016) found multicultural competence to be one of the most significant training needs for rehabilitation counselors with 67% agreement from respondents. In response, rehabilitation counseling programs must adapt their curricula to ensure students are provided with the knowledge and skills necessary to provide high quality services that are culturally responsive and sensitive.…”
Section: Diversity and Multiculturalismmentioning
confidence: 99%
“…Leahy et al 49 and Beveridge et al 11 to gauge rehabilitation counselors' training needs for core competencies identified for their professional group. These studies using the KVI-R were able to link scale ratings to practice settings, frequency of use in practice, and job functions.…”
Section: Kvi-r Subsequently the Kvi-r Was Used Bymentioning
confidence: 99%
“…Needs was also adapted from the KVI-R, 11,46 and listed eight transition service provider skills identified through the collaborative process, such as "Clarifying my role in interdisciplinary teams" and "Collaborating with providers to access resources for youth. " As with the competency instrument, participants used 5-point Likert-type scales to indicate the importance of the skill for their success in delivering transition services (1 = not at all important, 5 = very important), and their personal need for training (1 = not at all needed, 5 = very much needed).…”
Section: Transition Service Provider Skills Scale-importance and Traimentioning
confidence: 99%
See 1 more Smart Citation